2016
DOI: 10.1016/j.drugalcdep.2015.12.037
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an alcohol harm reduction intervention on interpersonal violence and engagement in sex work among female sex workers in Mombasa, Kenya: Results from a randomized controlled trial

Abstract: Aims To evaluate whether an alcohol harm reduction intervention was associated with reduced interpersonal violence or engagement in sex work among female sex workers (FSWs) in Mombasa, Kenya. Design Randomized controlled trial. Setting HIV prevention drop-in centers in Mombasa, Kenya. Participants 818 women 18 or older in Mombasa who visited HIV prevention drop-in centers, were moderate-risk drinkers and engaged in transactional sex in past six months (410 and 408 in intervention and control arms, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 33 publications
(51 reference statements)
1
51
0
Order By: Relevance
“…The Raising HIV Awareness in Non-HIV-Infected Indian Wives (RHANI) Wives intervention targeted women in urban Mumbai experiencing IPV and heavy spousal alcohol use, and the intervention included a focus on alcohol as a point of spousal conflict; however, changes in substance use patterns were not measured or reported [ 19 ]. A recent evaluation reported that an alcohol harm reduction intervention reduced exposure to interpersonal violence and engagement in sex work among a population of sex workers in Mombasa, Kenya [ 20 ]. Other evaluations of IPV-focused interventions have not analyzed substance use.…”
Section: Introductionmentioning
confidence: 99%
“…The Raising HIV Awareness in Non-HIV-Infected Indian Wives (RHANI) Wives intervention targeted women in urban Mumbai experiencing IPV and heavy spousal alcohol use, and the intervention included a focus on alcohol as a point of spousal conflict; however, changes in substance use patterns were not measured or reported [ 19 ]. A recent evaluation reported that an alcohol harm reduction intervention reduced exposure to interpersonal violence and engagement in sex work among a population of sex workers in Mombasa, Kenya [ 20 ]. Other evaluations of IPV-focused interventions have not analyzed substance use.…”
Section: Introductionmentioning
confidence: 99%
“…Most countries do not mention alcohol reduction interventions in their HIV/AIDS control programs [ 33 ]. In addition, only a few studies on alcohol reduction for HIV prevention have been done in SSA, the majority of which demonstrated short term reductions in alcohol consumption but inconsistent changes in sexual behavior and HIV risk [ 6 , 34 , 35 , 38 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…We know from the evaluation of the earlier Avahan programme that engagement with the CBO and visits from peer educators were associated with a reduction in violence experienced by sex workers from clients and the police 19 34. The positive engagement of the CBO during Avahan’s non-randomised implementation and the problematic engagement of the same CBO during Samvedana Plus implementation raise the question of whether it is wise to undertake a randomised trial in collaboration with a community-based group whose loyalty falls naturally with the well-being of its members.…”
Section: Discussionmentioning
confidence: 99%
“…One trial showed some effect of a brief alcohol intervention on reducing client violence but not IPV at 6 months. The authors attribute this differential outcome to the more complex relationships that sex workers have with their non-paying partners, which make them harder to change 19. The second used motivational interviewing to reduce client violence in the context of an HIV/sexually transmitted infection (STI) intervention.…”
Section: Introductionmentioning
confidence: 99%